Heterogeneous tax sensitivity of firm-level investments - Peter Egger; Katharina Erhardt; Christian Keuschnigg (Institute for Advanced Studies (IHS), 2014)
Firms are heterogeneous in size, productivity, ownership concentration, governance, financial structure and other dimensions. This paper introduces a stylized theoretical framework to account for such differences and to explain the heterogeneous tax sensitivity of firm-level investments across firm types. We econometrically test the theoretical predictions, taking account of selection of firms into different regimes. We find important differences in the tax sensitivity of investment of small entrepreneurial and larger managerial firms in different financial regimes that are largely in line with theoretical results.
Keywords: D22; G32; H25; L21; 330; Corporate tax; Personal taxes; Firm heterogeneity; Access to capital; Manager-shareholder conflicts